Inflexibility in Reasoning: Comparisons of Cognitive Flexibility, Explanatory Flexibility, and Belief Flexibility Between Schizophrenia and Major Depressive Disorder - Zhu, Chen; Kwok, Nate Tsz-kit; Chan, Tracey Chi-wan; Chan, Gloria Hoi-kei; So, Suzanne Ho-wai (Frontiers in Psychiatry, 2021)
Introduction. Inflexibility in reasoning has been suggested to contribute to psychiatric disorders, such as explanatory flexibility in depression and belief flexibility in schizophrenia. However, studies tended to examine only one of the flexibility constructs, which could be related to each other, within a single group of patients. As enhancing flexibility in thinking has become one of the psychological treatment goals across disorders, this study aimed to examine three constructs of flexibility (cognitive flexibility, explanatory flexibility, and belief flexibility) in two psychiatric groups. Methods. We compared three groups of participants: (i) 56 outpatients with a schizophrenia-spectrum disorder and active delusions, (ii) 57 outpatients with major depressive disorder and at least a moderate level of depression, and (iii) 30 healthy controls. Participants were assessed on symptom severity and flexibility, using the Trail-Making Task, the Attributional Style Questionnaire, the Maudsley Assessment of Delusions Scale (MADS) and the Bias Against Disconfirmatory Evidence (BADE) Task. Results. Cognitive flexibility was reduced in the two clinical groups than controls. Explanatory flexibility was comparable across groups. The three groups differed in belief flexibility measured by MADS but not by the BADE task. Response to hypothetical contradiction was less flexible in the delusion group than the other two groups, and the ability to generate alternative explanations was reduced in the delusion group than healthy controls. Discussion. We found an effect of clinical status on the more fundamental level of flexibility, which might be confounded by differences in intellectual functioning. Reduced belief flexibility tended to be specific to delusions.